Healthcare-Associated Ralstonia mannitolilytica Bacteremia from Contaminated Pantoprazole Diluent: A 34-Patient Case Series from India - Rangwala, Misbah; Reddy, Harsha (Journal of Neonatal Surgery, 2025)
Background: Ralstonia mannitolilytica is an emerging opportunistic pathogen capable of contaminating water-based medical products and causing healthcare-associated bloodstream infections. Outbreaks from India remain rare, and large series are seldom reported. Objectives: To describe the clinical, microbiological, and epidemiological characteristics of a 34-patient outbreak of R. mannitolilytica bloodstream infection in a tertiary-care centre and identify the contamination source. Methods: A retrospective outbreak investigation was conducted between 28 April and 17 May 2025. All patients with blood culture–confirmed R. mannitolilytica were included. Clinical data, antimicrobial susceptibility, and potential common exposures were analysed. Cultures of intravenous fluids, consumables, and medications were performed to identify the source. Results: Thirty-four patients (median age 44 years; 56% male) developed R. mannitolilytica bloodstream infection, with 55.8% admitted in the ICU. Polymicrobial infection occurred in 38%. Common comorbidities included sepsis (61.8%) and acute kidney injury (55.9%). Antimicrobial susceptibility showed sensitivity to cefoperazone–sulbactam, carbapenems, and fluoroquinolones, with resistance to piperacillin–tazobactam, aminoglycosides, colistin, and TMP-SMX. A single batch of pantoprazole diluent was identified as the contamination source, with unopened vials producing identical isolates. After the immediate withdrawal of the implicated batch and reinforcement of infection control measures, no additional cases were reported. The overall mortality rate was 20.6%, with deaths primarily resulting from underlying illnesses rather than the infection. Conclusion: This 34-patient cluster constitutes the most significant documented outbreak of Ralstonia mannitolilytica in India and the inaugural case associated with contaminated pantoprazole diluent. The event shows that the organism can live in water-based medicines, which shows how important it is to keep a close eye on medication sterility, look out for rare non-fermenters, and respond quickly to outbreaks with a team of experts to stop the spread..